(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the study was to identify the level of safety and the efficacy of flecainide per o.s. in patients with recent-onset (<48 hours) AF. The management of patients with recent-onset Atrial Fibrillation (AF) presenting at emergency departments varies widely. Materials and Methods: Eighty-one eligible, consecutive patients with AF were enrolled in a prospective, randomized study. Patients were randomly allocated in two groups: patients in Group A (41 patients, 28 Men – 13 Women, mean age 64.7+ 15.67 years), received flecainide 200mg and in case of no conversion an addition of 100 mg after one hour was given. In Group B (40 patients, 26 Men – 14 Women, mean age 67.5+18.74 χρόνων) a rate control strategy was adopted. The efficacy and safety of flecainide in 45 min, 60 min, 3-6 hours, 6-12 hours, 12-24 hours and 24-36 hours were studied. The primary endpoint for efficacy was time to cardioversion. The safety of flecainide was described by registration and monitoring of side effects. Results: Successful cardioversion was achieved in 37 patients (90.24%) from Group A versus 5 patients (12.5%) from Group B (p<0.0005). Cardioversion rate was 72.97% the first three hours in patients given flecainide and most of them were discharged from the hospital. Flecainide administration (OR=2.47 – p<0.0001) and patients’ heart rate on admission (OR=1.15 – p=0.04) were associated with the success of pharmacological cardioversion in 24 hours while negative prognostic factors were patients’ age (OR=1.08 – p=0.04), duration of AF (OR=0.94 – p=0.01) and left atrium size (OR=0.87 – p=0.04). There were no reported side effects. Conclusion: In carefully selected patients presenting with recent-onset AF and without structural heart disease the use of flecainide per os has shown a significant efficacy for cardioversion and has a low incidence of adverse effects.